2022
DOI: 10.3390/vaccines10060951
|View full text |Cite
|
Sign up to set email alerts
|

The AI-Assisted Identification and Clinical Efficacy of Baricitinib in the Treatment of COVID-19

Abstract: During the current pandemic, the vast majority of COVID-19 patients experienced mild symptoms, but some had a potentially fatal aberrant hyperinflammatory immune reaction characterized by high levels of IL-6 and other cytokines. Modulation of this immune reaction has proven to be the only method of reducing mortality in severe and critical COVID-19. The anti-inflammatory drug baricitinib (Olumiant) has recently been strongly recommended by the WHO for use in COVID-19 patients because it reduces the risk of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…Baricitinib was approved by the FDA in May 2022 for the treatment of COVID-19 in hospitalized adults requiring supplemental oxygen, non-invasive or invasive mechanical ventilation, or extracorporeal membrane oxygenation. The World Health Organization recommended its use for the treatment of COVID-19 patients because of its ability to reduce the risk of progressive disease and death [ 140 ]. Importantly, a study in elderly people (older than 70 years) demonstrated a reduction (18.5%) in the absolute mortality risk in the studied cohort [ 141 ].…”
Section: Therapeutics Against Sars-cov-2mentioning
confidence: 99%
“…Baricitinib was approved by the FDA in May 2022 for the treatment of COVID-19 in hospitalized adults requiring supplemental oxygen, non-invasive or invasive mechanical ventilation, or extracorporeal membrane oxygenation. The World Health Organization recommended its use for the treatment of COVID-19 patients because of its ability to reduce the risk of progressive disease and death [ 140 ]. Importantly, a study in elderly people (older than 70 years) demonstrated a reduction (18.5%) in the absolute mortality risk in the studied cohort [ 141 ].…”
Section: Therapeutics Against Sars-cov-2mentioning
confidence: 99%
“…Baricitinib has also been taken for brief periods by over one million seriously ill hospitalised patients with COVID-19. In meta-analyses, few, if any, drug-induced serious adverse events were reported in this patient population; in contrast, the drug showed significant mortality benefits even when added to other treatments such as steroids and tocilizumab [ 177 ]. In addition, the incidence of secondary infections with COVID-19 was reduced by 50% by baricitinib in the ACTT-2 clinical trial [ 178 ].…”
Section: Jak Inhibitorsmentioning
confidence: 99%
“…Vein thrombosis [30][31] Paxlovid (Nirmatrelvir-Ritonavir) Inhibition of viral replication Headache, diarrhea, vomiting dysgeusia [32] Molnupiravir (Lagevrio) Inhibition of virus multiplying Dizziness, rash, diarrhea, nausea [33][34] Kineret (anakinra) Inhibition of interleukin-1 (IL-1) receptor Reaction in injection site, enhancement of liver enzymes, hypertension [35][36] Gohibic (Vilobelimab) Vilobelimab as an antagonist od complement component 5a (C5-a) receptor, acts as anti-inflammatory agent Hypertension, pneumonia, pulmonary embolism, delirium, and sepsis [37] Prioritizing Potential Candidates for Anti-SARS-CoV-2 Drug Development and Discovery from Phytochemicals and Plant Secondary Metabolites…”
Section: Remdesivir (Veklury)mentioning
confidence: 99%
“…The repurposed antiviral drugs used to treat COVID-19 may provide protection against infection or speed up recovery, but all COVID-19 antiviral drugs currently on the market have drawbacks that may prevent their use by the general public [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. For example, remdesivir administration led to mild to moderate undesirable outcomes, including but not restricted to liver toxicity, queasiness, anemia, kidney impairment, low blood pressure, respiratory collapse, and constipation, among other things [38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%